2021
DOI: 10.1590/0103-8478cr20200855
|View full text |Cite
|
Sign up to set email alerts
|

Phytobiotic effect of Marrubium vulgare and Leonurus sibiricus on productive performance of griller-type broilers

Abstract: The food industry is in a continuous search for strategies of reducing of antibiotic residues in livestock production, given the development of antibiotic-resistant bacteria. In that context, there is a consistent increasing in the usage of alternative feed phytogenic additives. Due to the pharmacological, the plants Marrubium vulgare and Leonurus sibiricus, are both potential replacements for growth-promoting antibiotics. This study evaluated the productive performance and analyze the sensory qualities in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…M. vulgare extract also showed the inhibition of edema at 47.65% with the reference indomethacin producing 54.55% inhibition [26]. Based on these results, M.vulgare can be considered a prospect in the development of anti-inflammatory drugs [27].…”
Section: Anti-inflammatory Activitymentioning
confidence: 67%
“…M. vulgare extract also showed the inhibition of edema at 47.65% with the reference indomethacin producing 54.55% inhibition [26]. Based on these results, M.vulgare can be considered a prospect in the development of anti-inflammatory drugs [27].…”
Section: Anti-inflammatory Activitymentioning
confidence: 67%
“…Moreover, the application of this additive did not have a significant statistical effect on the change of meat colour ( L * a * b *) in the study groups. A study performed Schlemper et al [ 61 ] and Joseph et al [ 62 ] showed no effect of the addition of the phytobiotic on meat colour. On the other hand, Ashour et al [ 63 ] described that values of L* and a * grads of samples from broiler chicken were lower in a control group than in groups fed with a herbal mixture powder consisted of Capsicum annuum , Thymus vulgaris , Salvia Rosmarinus , Pimpinella anisum , Mentha spicata , Nigella sativa , Allium sativum .…”
Section: Discussionmentioning
confidence: 99%